Microfabrication of electrode-integrated liver-on-achip for in-vitro cell culture monitoring - Dalló, Luíse Cambruzzi (Universidade do Vale do Rio dos Sinos, 2025)
The liver is a vital organ responsible for crucial metabolic functions, drug metabolism, detoxification, and the production of proteins necessary for maintaining homeostasis in the body. However, studying liver physiology and drug metabolism has traditionally relied on animal models and two-dimensional (2D) cell cultures, which often fail to recapitulate the complex and dynamic nature accurately. Liver-on-a-chip is an emerging technology that aims to replicate the structure and functions of the human liver in a miniature and controlled in vitro platform. This study presents the fabrication and characterization of a liver-on-a-chip microfluidic device integrating microelectrodes for real-time cell culture monitoring. The device mimics the hepatic microenvironment by incorporating microchannels connected through endothelial-like capillaries, facilitating controlled nutrient exchange and waste removal under continuous perfusion conditions. The fabrication process involved three main stages: electrode fabrication, mold fabrication, and microchannel manufacturing. HepG2 cells were cultured within the microfluidic device under dynamic perfusion, demonstrating progressive adhesion, proliferation, and viability over multiple days. Impedance spectroscopy was employed to quantitatively assess cell behavior, with measurements indicating stable electrode performance and reliable monitoring of cellular dynamics. The results confirmed that the liver-on-a-chip device successfully supports long-term cell culture while providing real-time electrical characterization. This makes it a promising platform for hepatic disease modeling and pharmaceutical testing.
Keywords: Organ-on-a-chip; Liver-on-a-chip; Impedance spectroscopy; In-vitro; ACCNPQ::Engenharias::Engenharia Elétrica